A Systematic Review of Performance Enhancement of Humanitarian Logistics through Transparency: Current Status and Perspectives - Bae, Junghan; Khan, Muhammad; Lee, Hee Young (International Journal of Supply Chain Management, 2019)
The mechanism of how transparency can help to enhance the performance of humanitarian logistics (HL) following disaster relief operation (RO) needs to be explored. Thus, the main purposes of this paper are to systematically review the barriers to and benefits of transparency in the field of HL in order to improve the performance of HL, and also to highlight the role and unique attributes of transparency in the field of HL. A systematic literature review using the CIMO (context, intervention, mechanism, and outcomes) logic approach was adopted to perform the systematic analysis of the previous investigations relevant to the performance enhancement of HL. Most such previous research investigated transparency in the context of HL, with little examination of the outcomes of transparency in HL. Based upon this process, disaster risk can be reduced and managed through efficient HL. So far, the efficiency and performance of HL has been improved through coordination, collaboration and partnership. In the present study, recent developments corresponding to performance enhancement of HL through transparency are reviewed systematically, with a particular focus on the importance of transparency, what organizations can do to become more transparent and the challenges and potential benefits of transparency. The authors provide an in-depth understanding of the barriers and challenges to transparency faced in this field. Furthermore, the challenges in comparing with recent research are also discussed, along with future directions to improve the performance enhancement of HL through transparency. However, the poor performance of HL is one of the challenging issues associated with disaster risk management. This review article will be fruitful for novice researchers and practitioners in managing disaster risk through efficient HL and further advancement in the field of HL. Furthermore this article raises the awareness of the importance of carefully evaluating decisions related to the fair distribution of relief items.